Biological Bases of Seed and Vegetative Reproduction of Cornelian Cherry (Cornus mas L.) in Nature and Culture - Klymenko, Svitlana; Grygorieva, Olga; Onyshuk, Lyudmila (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
Cornelian cherry (Cornus mas L.) is a valuable fruit, medical, decorative, meliorative plant. It is rarely cultivated due to the lack of studies on ways of its seed and vegetative reproduction. In recent decades in Ukraine, as well as in other countries, interest on cornelian cherry has increased significantly, but the demand for cultivar planting material is not being satisfied because of insufficient knowledge of the tested methods of seed and vegetative reproduction. The department of Acclimatization of fruit plants of NBS works on breeding of cornelian cherry, the selection fund of which is represented by several dozen cultivars, 14 of them are entered in the State Register of Plant Cultivars of Ukraine. The methods of seed and vegetative reproduction have been studied. Despite the fact that the seed method of reproduction of the cornelian cherry has not lost its importance for growing the rootstock, as well as seedlings for the creation of forest cultures, during creating mono-gardens from cornelian cherry, vegetative reproduction of promising cultivars is necessary, since the seed method of reproduction doesn’t ensure the fixation of all economically valuable characteristics of the cultivars in the progeny. In addition, seedlings begin to bear fruit only for the 6th–8th year, and vegetative reproduced plants – for the 2nd–3rd year. Reproduction of the cornelian cherry in nature is caused by the enhanced ability to form the sprouts. This type of formation of young shoots has continued for many tens of years due to the continuous restoration of dying subordinate trunks. We have studied the reproduction of cornelian cherry by spring and summer grafting, lignified and summer cuttings. The emergence of the regenerative ability in the cutting depends on various endogenous and exogenous factors. In the average conditions cornelian cherry doesn’t reproduce well by cuttings. However, following factors such as high humidity, sufficient warmth, treatment of cuttings using physiologically active substances increase the percentage of rooting, the overall number of roots and their total length. Cuttings of 10–15 cm length should have 2–4 pairs of leaves. Leaves have a great value for cornelian cherry during the cuttings propagation: the leaf blade doesn’t get shorter, hence promoting the fast and intensive growth of roots, in comparison with traditionally prepared cuttings. By the end of the vegetative period the cornelian cherry rooted cuttings are weakly developed and thus are planted for cultivation in the early spring (end of March – beginning of April), with the planting scheme 20 × 35 cm. By the end of the II vegetative period the cuttings reach height of 70–80 cm, the diameter of the root stocks is 8–10 mm, the plants form 3–4 side shoots and can be planted to a permanent place. The ability of the cornelian cherry to form a large number of sprouts depends on its longevity. The most effective methods of vegetative reproduction are budding and green cuttings. The yield of planting material during the reproduction of the cornelian cherry by budding is 90–95%, the layers 85–90%, the green cuttings 75–80%, the lignified cuttings 40–60%, the spring graft 40–60%.